Cytomegalovirus detection is associated with ICU admission in non-AIDS and AIDS patients with Pneumocystis jirovecii pneumonia. - Alexandre Perret; Marion Le Marechal; Raphaele Germi; Daniele Maubon; Cécile Garnaud; Johan Noble; Aude Boignard; Loïc Falque; Mathieu Meunier; Théophile Gerster; Olivier Epaulard (PLoS ONE, 2024)
Objectives Cytomegalovirus (CMV) is frequently detected in lung and/or blood samples of patients with Pneumocystis jirovecii pneumonia (PJP), although this co-detection is not precisely understood. We aimed to determine whether PJP was more severe in case of CMV detection. Methods We retrospectively included all patients with a diagnosis of PJP between 2009 and 2020 in our centre and with a measure of CMV viral load in blood and/or bronchoalveolar lavage (BAL). PJP severity was assessed by the requirement for intensive care unit (ICU) admission. Results The median age of the 249 patients was 63 [IQR: 53-73] years. The main conditions were haematological malignancies (44.2%), solid organ transplantations (16.5%), and solid organ cancers (8.8%). Overall, 36.5% patients were admitted to ICU. CMV was detected in BAL in 57/227 patients; the 37 patients with viral load ≥3 log copies/mL were more frequently admitted to ICU (78.4% vs 28.4%, p<0.001). CMV was also detected in blood in 57/194 patients; the 48 patients with viral load ≥3 log copies/mL were more frequently admitted to ICU (68.7% vs 29.4%, p<0.001). ICU admission rate was found to increase with each log of BAL CMV viral load and each log of blood CMV viral load. Conclusions PJP is more severe in the case of concomitant CMV detection. This may reflect either the deleterious role of CMV itself, which may require antiviral therapy, or the fact that patients with CMV reactivation are even more immunocompromised.